Potential Impact of Aedes Albopictus (Skuse,1894), an Arbovirus and Nematode Vector, on Human Public Health - António, J. dos Santos Grácio; Maria, Amélia Grácio (Journal of Public Health International, 2019)
A review outlines the ecology and public health implications of Aedes albopictus as a vector of arboviruses and nematodes. Surveillance and control strategies are discussed.
Keywords: Aedes albopictus (Skuse; 1894); arbovirus; nematode; vector-borne diseases; public health